PENGARUH FREE CASH FLOW, PERTUMBUHAN PERUSAHAAN DAN KEBIJAKAN HUTANG TERHADAP DIVIDEND PAYOUT PADA PERUSAHAAN SEKTOR PERTANIAN YANG TERDAFTAR DI BEI PERIODE 2015 - 2019 - Ronaldo .; Sri Elviani; Syamsul Efendi (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2021)
The purpose of this study is to observe the relationship between free cash flow, debt policy and company growth with dividend payout. The type of research data used is a quantitative approach. Determination of the sample that can be used is purposive sampling technique, and there are 10 companies in the agricultural sector that become the research sample from 25 companies as a whole. The analytical technique used is multiple linear regression. The data source used is secondary data obtained from the Indonesia Stock Exchange, by taking financial reporting data, from 2015 to 2019. The results of this study state that individually the company's growth has a negative effect on dividend payout, then free cash flow and debt policies do not have influence with dividend payout. Meanwhile, simultaneously free cash flow, debt policy and company growth have no effect on dividend payout.